2022
DOI: 10.3389/fneur.2022.969047
|View full text |Cite
|
Sign up to set email alerts
|

Vertigoheel improves central vestibular compensation after unilateral peripheral vestibulopathy in rats

Abstract: The aim of this study was to assess the effect of Vertigoheel on central vestibular compensation and cognitive deficits in rats subjected to peripheral vestibular loss. Young adult male Long Evans rats were subjected to bilateral vestibular insults through irreversible sequential ototoxic destructions of the vestibular sensory organs. Vestibular syndrome characteristics were monitored at several time points over days and weeks following the sequential insults, using a combination of behavioral assessment parad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The mechanisms of VH-04 effects are not well elucidated, but may involve a stimulating effect on the central nervous system activity either via vasodilatation or direct modulation of neurons. Administration of VH-04 modulated frequency components of EEG in a manner similar to that of cognition-enhancing tacrine and metanicotine as well as caffeine ( Dimpfel et al, 2019 ) and seemed to improve cognitive performance in the eight-arm radial maze task of rats sham-treated for modeling vestibular syndrome ( Hatat et al, 2022 ). These observations suggested that VH-04 may have cognition-enhancing activity.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of VH-04 effects are not well elucidated, but may involve a stimulating effect on the central nervous system activity either via vasodilatation or direct modulation of neurons. Administration of VH-04 modulated frequency components of EEG in a manner similar to that of cognition-enhancing tacrine and metanicotine as well as caffeine ( Dimpfel et al, 2019 ) and seemed to improve cognitive performance in the eight-arm radial maze task of rats sham-treated for modeling vestibular syndrome ( Hatat et al, 2022 ). These observations suggested that VH-04 may have cognition-enhancing activity.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies, it was shown that Vertigoheel improves central vestibular compensation ( 8 ). However, the mechanism of action in BVP and FD is so far largely unclear and should be examined in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Vertigoheel is a natural non-prescription medicinal product containing four active ingredients for the treatment of vertigo and was approved by the German regulatory authority as a treatment for vertigo of various origins. According to recent research performed with rat models, Vertigoheel enhanced central vestibular compensation after unilateral peripheral vestibulopathy ( 8 ). Vertigoheel’s mode of action is not fully understood and under evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous or sequential bilateral administration of arsanilate makes it possible to reproduce bilateral vestibular areflexia reproducing those encountered in humans following massive administration of aminoglycosides or after heavy chemotherapy. Under these conditions, the animals also exhibit cognitive deficits of memory loss and spatial navigation [ 20 , 21 , 22 ] characteristic of those observed in patients with double vestibular areflexia [ 23 ].…”
Section: Animal Models Of Peripheral Vestibulopathiesmentioning
confidence: 99%